Lymphatic Endothelial-to-Myofibroblast Transition: A Potential New Mechanism Underlying Skin Fibrosis in Systemic Sclerosis - Irene Rosa; Eloisa Romano; Bianca Saveria Fioretto; Khadija El Aoufy; Silvia Bellando-Randone; Marco Matucci-Cerinic; Mirko Manetti (Cells, 2023)
At present, only a few reports have addressed the possible contribution of the lymphatic vascular system to the pathogenesis of systemic sclerosis (SSc). Based on the evidence that blood vascular endothelial cells can undertake the endothelial-to-myofibroblast transition (EndMT) contributing to SSc-related skin fibrosis, we herein investigated whether the lymphatic endothelium might represent an additional source of profibrotic myofibroblasts through a lymphatic EndMT (Ly-EndMT) process. Skin sections from patients with SSc and healthy donors were immunostained for the lymphatic endothelial cell-specific marker lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1) in combination with α-smooth muscle actin (α-SMA) as the main marker of myofibroblasts. Commercial human adult dermal lymphatic microvascular endothelial cells (HdLy-MVECs) were challenged with recombinant human transforming growth factor-β1 (TGFβ1) or serum from SSc patients and healthy donors. The expression of lymphatic endothelial cell/myofibroblast markers was measured by quantitative real-time PCR, Western blotting and immunofluorescence. Collagen gel contraction assay was performed to assess myofibroblast-like cell contractile ability. Lymphatic endothelial cells in intermediate stages of the Ly-EndMT process (i.e., coexpressing LYVE-1 and α-SMA) were found exclusively in the fibrotic skin of SSc patients. The culturing of HdLy-MVECs with SSc serum or profibrotic TGFβ1 led to the acquisition of a myofibroblast-like morphofunctional phenotype, as well as the downregulation of lymphatic endothelial cell-specific markers and the parallel upregulation of myofibroblast markers. In SSc, the Ly-EndMT might represent a previously overlooked pathogenetic process bridging peripheral microlymphatic dysfunction and skin fibrosis development.